Cystic adrenal masses: spectrum of multimodality imaging features and pathological correlation. Issue 7 (July 2022) - Wang, M.X.; Mahmoud, H.S.; Klimkowski, S.; Salem, U.; Korivi, B. Rao; Corwin, M.; Ahmed, A.M.; Shaaban, A.M.; Menias, C.O.; Elsayes, K.M.
Abstract : Adrenal cystic lesions are generally rare and encompass a wide spectrum of benign and malignant entities. Increased utilisation of cross-sectional imaging has led to increased detection of incidentally discovered adrenal lesions. Many of these lesions are cystic or solid with cystic changes, and the majority are benign; however, some may represent malignant lesions and/or even metastases. Therefore, it is vital to characterise these lesions appropriately and follow-up with laboratory tests and imaging if necessary. Key imaging techniques include computed tomography (CT) and magnetic resonance imaging (MRI). Other supplemental imaging tools include metaiodobenzyl-guanidine (MIBG) scintigraphy and 2-[ 18 F]-fluoro-2-deoxy-d- glucose positron-emission tomography (FDG-PET). Accurate diagnosis of adrenal cystic lesions is crucial in guiding appropriate evaluation and management of these patients. This review highlights the clinical presentations, pathological and imaging features, and management of cystic adrenal lesions.